Characteristics Of Neurogenic Shock - Wulan Apriliantisyah; Lilian Triana Limoa; Sumarni, Sumarni (Jurnal EduHealth, 2024)
Shock is a circulatory disorder which is defined as a condition of inadequate oxygen transport to tissues or perfusion caused by hemodynamic disorders. One type of shock, namely neurogenic shock, which is a form of distributive shock, is a critical condition resulting from dysregulation of the autonomic nervous system after spinal cord injury, especially in the cervical and upper thoracic vertebrae above T6, as a result of a traumatic event.. Worldwide , neurogenic shock occurs between fifteen and fifty-two events per million people annually with a higher incidence of cervical spine injury (SCI) (29%) compared to thoracic injury (19%). This causes hypotension and bradycardia, classic signs of neurogenic shock. There are no universally established hemodynamic parameters for neurogenic shock. However, most studies adopted the criteria of systolic blood pressure below 90 mmHg and heart rate below 80 bpm. Patients with neurogenic shock may also manifest as pink, warm skin due to dilation of subcutaneous blood vessels. Treatment of patients with neurogenic shock requires vasopressor drugs such as noradrenaline, phenylephrine, or metaraminol, and positive inotropic dopamine is recommended to treat vascular tone and prevent secondary injury. .